Effect of age and social connection on perceived anxiety over radiation exposure among decontamination workers in Fukushima Prefecture, Japan. Issue 2 (25th May 2016) - Hidaka, Tomoo; Kakamu, Takeyasu; Hayakawa, Takehito; Kumagai, Tomohiro; Jinnouchi, Takanobu; Sato, Sei; Tsuji, Masayoshi; Nakano, Shinichi; Koyama, Kikuo; Fukushima, Tetsuhito
Abstract : Objectives: To reveal the effect of age and other factors on perceived anxiety over radiation exposure among decontamination workers in Fukushima Prefecture, Japan. Methods: Asurvey questionnaire was sent to 1505 workers, with questions regarding age, presence of a written employment contract, previous residence, radiation passbook ownership, presence of close persons for consultation, knowledge of how to access public assistance, and a four‐point scale of radiation‐related anxiety (1 = " Very much, " 2 = " Somewhat, " 3="A little bit, " and 4="None"). The relationships between the degree of anxiety and variables were analyzed using the chi‐square test and residual analysis. Results: In all, 512 participants responded to the questionnaire. The mean age of participants was 46.2 years (SD: 13.1, range: 18‐77). Of them, 50, 233, 168, and 61 workers chose "Very much, " "Somewhat, " "A little bit, " and "None, " respectively, on the anxiety scale. Chi‐square test showed that participants aged 61 years and over had higher degrees of anxiety ( p <0.001). Ordinal logistic regression showed that the degree of anxiety increased if they did not have a written contract ( p =0.042) or persons to consult ( p =0.034) and if they routinely checked the dose rate ( p =0.046). Conclusions: Decontamination workers who do not have a written contract or who are in socially isolated situations have greater anxiety over radiation exposure. Thus, it is important to both create supportive human relationships for consultation and enhance labor management in individual companies.